Analisis Sistem Pemasaran Agribisnis Produk Ikan Asap di Jawa Tengah - Indrajit Wicaksana (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2022)
This study aims to determine the marketing system of smoked fish products with the marketing channel method and analyze the marketing efficiency of smoked fish products with the marketing margin and farmer share approach. The results of the analysis show that there are three marketing channels for smoked fish products which include fishermen, wholesalers, collectors, processors, retailers, food stalls and restaurants. Each actor gets the amount of marketing margin in accordance with the core activities with the core activities they have done. The difference in the value of marketing margin and farmer share in each channel indicates that marketing efficiency is relative. The marketing system for smoked fish products is relatively efficient in each marketing channel as long as each actor enjoys a large marketing margin and has considered the costs incurred. Keywords: agribusiness, farmer share, smoked fish, marketing margin, fishery